Фактори ризику для здоров’я населення в урбанізованих регіонах на прикладі промислового м. Запоріжжя та області - Соколовська, Ірина Анатоліївна; Sokolovskaya, I. A. (My University, 2018)
Актуальність. Псоріаз у всіх його різних клінічних формах — одне з найпоширеніших хронічних запальних захворювань шкіри. Для більшості пацієнтів, це означає багаторічні обмеження щодо різних аспектів повсякденного життя з величезними особистими витратами, а іноді і з тяжкою стигматизацією та дискримінацією. Соціально-економічні наслідки псоріазу пов’язані з його хронізацією, зниженням продуктивності праці та значними витратами на лікування. Захворювання може виникати як в дитячому, так і в дорослому віці, характеризується тривалими рецидивами, повною або частковою втратою працездатності, високими рівнями інвалідизації та соціально-психологічної дезадаптації пацієнтів. Ризик виникнення та складність перебігу значно зростає при несприятливих умовах зовнішнього середовища. Мета. Вивчити фактори ризику виникнення і поширення захворюваності на псоріаз у населення Запоріжжя і області в умовах впливу несприятливих екологічних чинників довкілля. Методи дослідження: гігієнічні, клініко-лабораторні, функціональні, епідеміологічні, статистичні. Relevance. Psoriasis in all its various clinical forms is one of the most common chronic inflammatory skin diseases. For most patients, the disease means long-term constraints in various aspects of everyday life with huge personal costs, and sometimes severe stigma and discrimination. Socio-economic consequences of psoriasis associated with its chronization, reduced labor productivity and significant costs of treatment. The disease can occur both in children and in adulthood, characterized by long-term relapse, total or partial loss of disability, high levels of disability and socio-psychological maladaptation of patients. The risk and complexity of the flow increases significantly under adverse environmental conditions. Purpose: on the basis of social and hygienic monitoring, to study the peculiarities of the psoriasis incidence of the population of the Zaporizhia region under the conditions of adverse ecological environmental factors. Methods of Research: hygienic, clinical-laboratory, functional, epidemiological, statistical. The results obtained and their novelty: for the first time, a systematic approach to the analysis of the incidence of psoriasis with regard to environmental factors has been used. Research results can be used in the implementation of modern technologies of social and hygienic monitoring to assess the state of health of the population with the identification of general patterns of prevalence of psoriasis. Conclusions. Human health is determined by the interaction of a number of factors: the quality of the environment, lifestyle, heredity, the presence of bad habits, socio-economic and psychological well-being, availability of medical care. The airspace occupy the first place (66,7 %), the second — food products (13,5 %) and the third — noises (12,6 %).
Risk factors for population health in urbanized regions on industrial example of zaporizhia and region
Keywords: соціально-гігієнічний моніторинг; псоріаз; методи дослідження; екологічні фактори; профілактика захворювань; social-hygienic monitoring; psoriasis; research methods; ecological factors; disease prevention